Estimates of Healthcare Spending for Preterm and Low-Birthweight Infants in a Commercially Insured Population: 2008–2016. Issue 12 (December 2020) - Beam, Andrew L.; Fried, Inbar; Palmer, Nathan; Agniel, Denis; Brat, Gabriel; Fox, Kathe; Kohane, Isaac; Sinaiko, Anna; Zupancic, John A. F.; Armstrong, Joanne
Abstract : (Abstracted from J Perinatol 2020;40:1091–1099) Preterm birth and low birthweight incur large medical, social, and economic costs on affected families and the US health care system. A 2007 study from the Institute of Medicine estimated that the total cost associated with preterm delivery in the United States was at least 26.2 billion annually or 51, 600 per infant born preterm.